2020
DOI: 10.1111/dom.14160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucagon‐like peptide‐1 receptor agonists liraglutide and semaglutide on cardiovascular and renal outcomes across body mass index categories in type 2 diabetes: Results of the LEADER and SUSTAIN 6 trials

Abstract: Associations between body mass index (BMI) and the cardiovascular (CV) and kidney efficacy of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in patients with type 2 diabetes (T2D) are uncertain; therefore, data analysed separately from the Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) trial and the Trial to Evaluate Cardiovascular and Other Long-term Outcomes with Semaglutide in Subjects with Type 2 Diabetes (SUSTAIN 6) were examined. These internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 18 publications
2
32
0
3
Order By: Relevance
“…Importantly, controlling inflammation is believed to contribute in the prevention of cardiovascular diseases ( 123 ). In one study, liraglutide and semaglutide were reported to mitigate the development of plaque lesions by changing the inflammatory pathway in a mouse model of AS ( 124 ). Besides, GLP-1RAs might be driven by anti-inflammatory mechanisms to inhibit the formation of macrophage foam cells and thus slow down the pathological processes of AS ( 125 , 126 ).…”
Section: Effects On Atherosclerosismentioning
confidence: 99%
“…Importantly, controlling inflammation is believed to contribute in the prevention of cardiovascular diseases ( 123 ). In one study, liraglutide and semaglutide were reported to mitigate the development of plaque lesions by changing the inflammatory pathway in a mouse model of AS ( 124 ). Besides, GLP-1RAs might be driven by anti-inflammatory mechanisms to inhibit the formation of macrophage foam cells and thus slow down the pathological processes of AS ( 125 , 126 ).…”
Section: Effects On Atherosclerosismentioning
confidence: 99%
“…A significant decrease in albuminuria, new onset of persistent proteinuria, and no progression of eGFR decline have been reported in diabetic patients. SUSTAIN-6 with semaglutide [96], another member of the GLP1 agonist class, reduces the risk of composite renal outcome largely driven by persistent proteinuria. However, Dulaglutide in the AWARD-7 [97] did not find differences in the reduction of albuminuria.…”
Section: Raas Blockersmentioning
confidence: 99%
“…Im Jahr 2020 wurde die EMPEROR-Reduced-Studie publiziert, die ausschließlich herzinsuffiziente Patienten mit NYHA-Stadien II, III oder IV mit einer Ejektionsfraktion ≤ 40 % mit und ohne Typ‑2-Diabetes einschloss. Die Probanden wurden neben der Standardtherapie entweder mit Empagliflozin 10 mg/Tag oder Plazebo behandelt [ 26 ]. Der primäre Endpunkt war eine Kombination von kardiovaskulärem Tod oder Hospitalisierung wegen sich verschlechternder Herzinsuffizienz.…”
Section: Hemmer Des Natrium-glukose-kotransportsunclassified